Implementasi Pendidikan Humanisme Religiusitas dalam Pendidikan Pendidikan Agama Islam di Era Revolusi Industri 4.0 - Devy Habibi Muhammad (Universitas Muhammadiyah Enrekang, 2020)
This study aims to explore the basic concept of humanismeme education as education so that children consciously have a religious character with an Islamic perspective and have an implementation in the learning process. So an approach is needed, a discussion method that includes deductive methods, inductive methods, comparative methods, and descriptive methods. Second, using library research, by collecting information from relevant reading materials, magazines, books, seminars and others, after which it is carefully studied and researched then the data is generalized and sorted according to the suitability of the research theme, then the data obtained from the sorting results are then analyzed. in depth with the method of analysis. Based on the results of the researcher's analysis, the concept of humanism education is an educational concept originating from the assumption that humans basically have almost the same potential which must be developed intensively and continuously, so that humanist religiosity education has relevance to the era of the industrial revolution 4.0. Humanism education directly invites students to find solutions to problems faced with guidance and direction from educators. The implementation of this concept emphasizes on educators so that they can create a learning environment that is far from the elements of coercion, oppression, hegemony of thought, and attitudes that are far from universal values ​​of monotheism and humanity.